Production and Marketing Problems Faced by Dry Grape Producers of Karnataka - Yarazari, Shivananda P.; Singh, Arun Kumar; Maji, Saikat (Indian Journal of Extension Education, 2022)
The study was an “ex post-facto” research carried out in Vijayapura district of Karnataka State during the year 2020-21. Two taluks were purposively selected based on the highest production of dry grapes to make a sample size of 200. The collected problems were analyzed using Garret’s ranking methodology to develop a quantitative position of each problem. The findings showed that dry grape producers faced production and marketing problems more severely. Among the production problems, heavy investment on inputs, no standard package of practices available from agriculture or horticulture universities and high rate of interest were prominent. Similarly, in the case of marketing problems, no local market and lack of processing and storage units were ranked at top. There is an immediate need to improve various marketing practices by developing a strategy in order to overcome these impediments which will enhance the entrepreneurial access of the dry grape producers.
Keywords: Market; Package of practice; Problems; Production and Strategy